Challenges of Conserving and Co-Managing Khadimnagar National Park and Ratargul Fresh Water Swamp Forest in Bangladesh - Mahfuz-Ur-Rahman, Md.; Dey, Tanmoy (Journal of Forests, 2021)
National Parks are protected areas conserving all types of flora, fauna and their habitats regardless of generic diversification. In Bangladesh, protected area managers face difficulties to conserve these areas. This study is formulated to find out those existing difficulties against effective co-management of natural resources based on the local people’s perception. A purposive sampling is followed by a semi-structured interview to gather data from the field level of Khadimnagar National Park and Ratargul Fresh Water Swamp Forest from September 2019 to December 2019 by interviewing 100 local people for RFWSF and KNP on the basis of a qualitative research method. Both inhabitants and the Forest Department are found to be responsible for inhibiting the effective management of the subjected areas meanwhile difficulties related to motivation, cordiality, alternative job generation, financial support to management authority, tourism management and resource extraction from forests mainly prevail. To ensure substantial sustainability, both of the actors should come forward to find out a way to get rid of this devastation and to ameliorate the socio-economic condition of these areas. Arranging more conferences to raise motivation, awareness about the forest offenses and generating alternative sources of income can be counted as a strategy to reduce pressure on both forests.